Comparative tests of chimney caps on the example of TRN-150 and T-22 -160 - Deska, Adam; Rubnikowicz, Adam (Instal, 2020)
The article presents the comparison of the test results of two chimney caps: one of the most commonly used TRN chimney cap and the new chimney cap type T-22. The schemas of the chimney caps, range of the tests and the scheme with description of the test stand are presented. The study presents the method of tests carried out. The research of chimney caps was carried out in the vertical and horizontal planes. Charts were constructed and negative pressure was applied as a function of the volume of ventilation air. The results of tests of the chimney caps resistance coefficients are also presented. The measurements results are discussed in the conclusions.
Keywords: natural ventilation; gravity ventilation; chimney caps